2023
DOI: 10.1039/d2fd00131d
|View full text |Cite
|
Sign up to set email alerts
|

The “η-sweet-spot” (ηmax) in liquid-assisted mechanochemistry: polymorph control and the role of a liquid additive as either a catalyst or an inhibitor in resonant acoustic mixing (RAM)

Abstract: Resonant Acoustic Mixing (RAM) offers a simple, efficient route for mechanochemical synthesis in the absence of milling media or bulk solvents. Here, we show the use of RAM to conduct...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
29
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 79 publications
0
29
0
Order By: Relevance
“…Furthermore, we found that the higher the η-value, the more p-HAP is formed. From this, we conclude that with 0.1 we have hit a sweet spot 37 with which we can achieve both high conversion and selectivity while also predominantly forming the desired p-HAP.…”
Section: Reaction Development In the Ball Millmentioning
confidence: 74%
“…Furthermore, we found that the higher the η-value, the more p-HAP is formed. From this, we conclude that with 0.1 we have hit a sweet spot 37 with which we can achieve both high conversion and selectivity while also predominantly forming the desired p-HAP.…”
Section: Reaction Development In the Ball Millmentioning
confidence: 74%
“…73 The systematic analysis of the coupling reactions conducted by RAM, as well as ball milling, revealed the appearance of an "η sweet-spot", i.e., an η-value at which the reaction conversion at a given time achieves a maximum (Figure 3). 73,74 Single time point analysis has been used extensively in development and screening of mechanochemical organic synthesis, with recent examples including screening of the catalyst and reaction scope for catalytic coupling of an amine, aldehyde, and acetylene 75 ("A3 coupling", Figure 4), creation of a protocol for mechanochemical ruthenium-catalyzed olefin metathesis, or development of a solvent-free activation of noble metals. 76,77 Notably, single time point analysis was used by the Mack and Blair groups to gain fundamental insight into energy delivery in mechanochemical reactions, by recording the conversion of Diels−Alder reactions conducted in milling assemblies made of different materials and at different frequencies.…”
Section: Monitoring Reactions At a Single Time Pointmentioning
confidence: 99%
“…The systematic analysis of the coupling reactions conducted by RAM, as well as ball milling, revealed the appearance of an “η sweet-spot”, i.e., an η-value at which the reaction conversion at a given time achieves a maximum (Figure ). , …”
Section: Monitoring Milling Reactionsmentioning
confidence: 99%
“…1E). Attempts to further optimize the reaction through screening η -values between 0 and 1.5 μL mg −1 revealed maximum conversion ( η max ) 14 at η = 0.25 μL mg −1 (Fig. 1D).…”
mentioning
confidence: 99%